Pengaruh corporate social responsibility dan green innovation terhadap kinerja keuangan perusahaan - Saputra, Adi Hasan Ragil; Rini, Endang Sulistya; Absah, Yeni (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2024)
Business activities in a company in the era of globalization are required to be more competitive and sustainable. This research aims to understand the influence of corporate social responsibility and green innovation on company financial performance. This research collects secondary data from companies registered as LQ-45 which are listed on the Indonesia Stock Exchange while also participating in the public information disclosure program regarding environmental compliance (PROPER) during 2021-2022 based on the structural equation modeling (SEM) method. The results of the study state that the variables intellectual capital, corporate social responsibility and green innovation have a significant effect on financial performance. Meanwhile, corporate social responsibility has no effect on green innovation. The corporate governance moderating variable has a significant effect on corporate social responsibility on financial performance. These findings can help stakeholders to maintain the sustainability of business and achieve competitive business advantages in order to increase company profits.